Efficacy of intravenous immunoglobulins in the prophylaxis of neonatal sepsis - S, Sharif; C, Bloomer; N, Al Assaf; R, Khan (Journal of Advanced Pediatrics and Child Health, 2021)
Despite critical care advances, robust antibiotic therapy and improved strategies in early detection and prevention of infection, the incidence of morbidity and mortality from neonatal sepsis worldwide in preterm and low birth weight neonates remains overwhelmingly high. Neonatal sepsis is characterised by a clinical syndrome of systemic signs of infection and bloodstream bacteraemia in newborns within the first months of life. The risk of sepsis in neonates is inversely proportional to gestational age and birth weight due to deficiency in humoral immunity and the need for more invasive supportive neonatal intensive care unit interventions. Adverse effects such as necrotising enterocolitis associated with antimicrobial therapy are serious enough to warrant exploration of alternative therapeutic strategies. Immunoglobulin replacement therapy offers hope of enhancing immune competence and reducing infection rates in vulnerable populations. It is evident from the relevant studies to date that the benefits offered by intravenous immunoglobulin prophylaxis may not be significant enough for routine hospital implementation. Further research to better understand the mechanisms underlying immunodeficiency will lead to the realisation of alternative therapeutic and prophylactic interventions.